PENGEMBANGAN KOMODITI PANGAN LOKAL MENJADI PRODUK WISATA KULINER DI KABUPATEN BANGLI, BALI - Ni Putu Eka Trisdayanti (JURNAL GASTRONOMI INDONESIA, 2018)
The introduction of Indonesian local food to tourists, in addition to adding tourist attraction but also as a basis for building a pro-people economy. However, until now the development of culinary tourism by utilizing local products for sustainable tourism has not been optimal. In this study aims to identify the local food commodity of Bangli Regency then developed into a culinary tourism product and test the quality of the product from the aspect of appearance, taste, and nutritional content. The technique of collecting data in this research is field survey to identify local food commodity of Regency of Bangli, then experiment in the form of the culinary tourism product. Experimental results tested the quality of food from the appearance, taste, aroma, texture of processed products culinary tourism with the organoleptic test. Next culinary tourism product of Bangli Regency counted nutritio content. Data analysis technique in this research is descriptive qualitative. The results of research that is from a variety of local products in Bangli Regency, appointed 3 leading commodities developed into a culinary tourism a product that is Mujair Fish processed into Mujair Nyat-nyat, Pepes Fish Mujair, Mujair Bakar; bananas processed into the banana cake, banana chocolate cheese, banana chips, banana pudding; Oranges are processed into marmalade, and orange juice. In general, the assessment of the products developed in the category of good, especially on the preparation of fish mujair with good taste, strong aroma, and appearance that arouse consumer’s taste. Culinary tourism products from local food commoditieshigh nutrient content.